Writing narrative essays using e-book writing software: analyses of students’ digital written works - Kee, Li Li; Razali, Abu Bakar; Baki, Roselan (AsiaTEFL, 2019)
This study explores the utilization of e-book writing software as a tool for process-based writing approach to enhance the learning of ESL writing among the pre-service teachers. The study adopted a qualitative research design which was conducted using document analysis technique on digital written works of six pre-service teachers in one Institute of Teacher Education Malaysia (ITEM). The pre- service teachers were introduced to narrative essay format and i-Spring Pro 6.2 software to produce e-books. The data gathered (i.e., pre-service teachers’ digital written works) were analyzed using predetermined (i.e., a priori) codes. As induced from the findings, the utilization of e-book writing software as a tool for process-based writing approach is found to enhance the learning of ESL writing among the pre-service teachers, which is evident from their improved accuracy of genre and message,fulfillment of task requirements, use of grammar, spelling, and punctuation, originality, coherence and organization, and use of multimedia in text presentation. These positive results indicate that the utilization of e-book writing software as a tool for process-based writing approach in writing narrative essay type is beneficial to expose pre-service teachers to a more meaningful, fun, and engaging way of learning and practicing ESL writing.